THE RELATIONSHIPS AMONG DIFFERENT PERFORMANCE MEASURES IN INDONESIAN RETAIL CONTEXT - Soehadi, Agus w. (Gadjah Mada International Journal of Business, 2002)
Despite research into the links between market orientation and firm performance, research into the detail different measures of performance has been limited. This study develops different measures of performance in retail business and examines their relationship with market orientation. The results suggest that market orientation positively relate to nonfinancial indicators.Â  Also, indirect nonfinancial indicator can be treated as dominant mediator for the relationship between market orientation and financial indicator. Further, the findings suggest that different types of performance measurement affect the magnitude of market orientation and performance association.